Sparsity-promoting optimal control for a class of distributed systems - Fardad, Makan; Fu Lin; Jovanovic, Mihailo R. (Proceedings of the 2011 American Control Conference, 2011)
We consider a linear quadratic optimal control problem with an additional penalty on the number of communication links in the distributed controller. We reformulate this combinatorial optimization problem as a sequence of weighted l 1 problems, where the weighted l 1 norm approximates the counting of the communication links. We identify a class of systems for which the weighted l 1 problem can be formulated as a semideflnite program and therefore its solution can be computed efficiently. Application of the developed algorithm to the optimal control of vehicular formations reveals communication topologies that become sparser as the price of inter-vehicular communications is increased.